Effect of ultraviolet post-curing, laser power, and layer thickness on the mechanical properties of acrylate used in stereolithography 3D printing. (1st February 2023) - Zeng, Yu-Shan; Hsueh, Ming-Hsien; Hsiao, Te-Ching
Abstract: Three-dimensional (3D) printing technology has developed rapidly in the past few years. This technology is widely used in houses, workpieces, artworks, organs, and even the food industry. Among the multiple 3D printing methods, the stereolithography appearance (SLA) technique is well known for its high printing speed and considerable accuracy. In this research, the optimization parameters of the laser curing technology were applied by changing laser power and molding thickness. The mechanical properties were tested using a tensile test and a compression test of photosensitive resin materials after ultraviolet (UV) curing. The experimental results revealed that increasing the laser power or reducing the molding thickness increased the ultimate tensile strength, tensile Young's modulus, and compressive strength of the material. However, when the stretch was decreased after UV curing, the strength of the material effectively improved, but the toughness of the material decreased. The abovementioned experimental results will be helpful to researchers for further studies on SLA.